Kodifikasi Al-Qur’an (Rasm Al-Qur’an dan Tujuh Qiraat Al-Qur’an) - Sholihatunnajah; Nisa Oktriana; Muhammad Abdul Hasyim (Edupedia Publisher, 2024)
This paper aims to find out about the writing patterns and ways of reading the holy Qur'an. This research is a type of library research by analyzing some data that is used as a reference or reference material for the information outlined in this article. The results of this study show, 1) Codification of the Qur'an; 2) Rasm of the Qur'an; 3) Seven Qiraat of the Qur'an.